Vegetable Crops - Health Benefits and Cultivation 2022
DOI: 10.5772/intechopen.100236
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable Proteins: Nutritional Value, Sustainability, and Future Perspectives

Abstract: The growing world population demands more production of proteins for healthy growth and prevention of protein-energy malnutrition. The animal proteins are not sufficient to meet the requirement of daily proteins intake. Furthermore, due to limited resources of animal number, land, water, environmental impact, the demand for vegetable proteins and sustainability have been increasing tremendously. This chapter will outline the demand scenarios of vegetable proteins, nutritional aspects, and technological challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This is owing to the growing world's population which stands at around 6.5 billion and is expected to double by the year 2063. This increased demand for root vegetable protein is further corroborated statistically as two-thirds of the planet's dietary protein comes from vegetables [4]. There exist a broad range of biological activities exhibited by bioactive proteins, and these activities are responsible for their application and interest in foods, supplements, and medicine [5].…”
Section: Introductionmentioning
confidence: 90%
“…This is owing to the growing world's population which stands at around 6.5 billion and is expected to double by the year 2063. This increased demand for root vegetable protein is further corroborated statistically as two-thirds of the planet's dietary protein comes from vegetables [4]. There exist a broad range of biological activities exhibited by bioactive proteins, and these activities are responsible for their application and interest in foods, supplements, and medicine [5].…”
Section: Introductionmentioning
confidence: 90%
“…Freeze-drying is a popular method for dehydrating plant-based goods, such as spices, fruits, vegetables, and some unusual meals. Despite its lengthy process time and hefty cost, it is favored for its best final quality [3,48,49].…”
Section: Freeze-dryingmentioning
confidence: 99%
“…Perhaps dehydration is chemical science's oldest and most versatile way of drying procedures [2]. The fruit has many valuable chemicals, making it an essential element of the human diet [3]. Since the moisture content of fresh fruits exceeds 80%, they are considered perishable foods [4].…”
Section: Introductionmentioning
confidence: 99%
“…Stress in the endoplasmic reticulum (ER) has been linked to inflammatory pathways. EAE has been demonstrated to enhance the expression of the ER stress genes XBP-1/s [ 115 ]. Crocin administration on day 7 after EAE induction decreased the expression of ER stress genes XBP-1/s and repressed ER stress and inflammatory gene expression in the spinal cord [ 116 ].…”
Section: Therapeutic Benefits Of Saffron In Brain Diseasesmentioning
confidence: 99%
“…According to studies, saffron aqueous extract (50, 100, 150, and 250 mg/kg) enhanced brain dopamine levels in a dose-dependent way. Furthermore, the extract showed no influence on serotonin or norepinephrine levels in the brain [ 115 , 117 ]. Furthermore, the findings revealed that the aqueous extract of saffron, at a concentration of 250 mg/kg, activated and boosted the synthesis of essential neurotransmitters such as dopamine and glutamate in the rat brain [ 117 ].…”
Section: Therapeutic Benefits Of Saffron In Brain Diseasesmentioning
confidence: 99%